Estudo de germinação em azinheira (Quercus rotundifolia Lam.) - Ribeiro, M M A; Elvas, P S (I Congresso Florestal Hispano-Luso, 21 a 27 Junho 1997. Pamplona, 1997)
In April 1996 a germination trial took place in Serra da Malcata Natural Reserve nursery. The acorns were collected in Malpica do Tejo holm oak stands, after fruit repining. Treatments included naked root plant production in normal nursery soil and plant production with different other methods: two different containers (plastic bag and plastic pot) with five different media composition (pine bark, peat, normal nursery soil, pine bark with perlite (1:1 v/v) and peat with perlite (1:1 v/v). The number of germinated seeds (G) per treatment and block was first recorded by the end of June and afterwards three times, every three weeks. Last time data was recorded, the following parameters were included: diameter (D) at soil level, height (H) and the leaf area (A), per plant. Percent of germination was better in every treatment using plastic pots, whatever the media used, and the worst results were achieved with the plastic bag/peat and naked root methods. On the other hand, the use of the plastic bag promoted plant loss, avoided with plastic pots. The best-scored treatments for the average plant diameter (D) were the pot/peat (3,26 mm) and bag/pine bark (2,92 mm) methods, and the bag/nursery soil produced the worst result (2,4 mm). The best/worst result in the mean height for plant (H), was obtained with the naked root (10,5 cm)/plastic pot with nursery soil (5,9 cm) method. The leaf area per plant (A) was 52 cm2 for the naked root method, higher then the value of this parameter in every other treatment, except in the bag/pine bark one (45 cm2 ).
Keywords: container; germination; Holm oak; media; naked root; Quercus rotundifolia Lam